Nonmetallic Minerals and Rocks Tax: an Analysis of The Effect Contribution on The Original Income in The Malaka Regency - Marisa S B Seran (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to determine the contribution of Nonmetallic Minerals and Rocks Tax to the Regional Original Income (PAD) of Malacca Regency. Using secondary data obtained from BPKAD Malacca Regency in 2016-2020. The model used is an analysis of ratios related to the tax contribution of nonmetallic minerals and rocks. The results showed that the Contribution of Nonmetallic Minerals and Rocks Tax contributed significantly to the Regional Tax of Malacca Regency from 2017 to 2020 where in 2017 the ratio of the contribution of Nonmetallic Minerals and Rocks Tax to the Pad of Malacca Regency was 19.60% included in the Less category, in 2018 the Contribution of Nonmetallic Minerals and Rocks Tax to the PAD of Malacca regency was 5.13% included in the category of very less, The contribution of Nonmetallic Minerals and Rocks Tax to PAD in 2019 of 84.71% is in the Very Good category and in 2020 the Contribution of Nonmetallic Mineral and Rock Tax on PAD of Malacca Regency is 24.60% and is included in the Medium category.